Preparation method, product and application of 3D hydrangea-shaped electrode material

Synthesis of 3D hydrangea electrode material CoAl-LDH@Ce-MOF through hydrothermal reactions solves the problem of insufficient performance of existing supercapacitor electrode materials, achieves high specific capacitance and long-term stability, and promotes its application in the fields of renewable energy and power storage.

CN119694808AActive Publication Date: 2025-03-25HUAINAN NORMAL UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510213324.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-03-25
Estimated Expiration
2045-02-26

AI Technical Summary

Technical Problem

The narrow voltage range and low energy density of existing supercapacitors limit their wider applications, especially in the fields of renewable energy and power storage.

Method used

A 3D hydrangea electrode material CoAl-LDH@Ce-MOF was synthesized through hydrothermal reaction, and the specific capacitance and cyclic stability of the electrode material were improved by using the synergistic effect of CoAl-LDH and Ce-MOF.

Benefits of technology

This electrode material significantly improves capacity performance and electrochemical stability, with a capacitance retention rate of 88.5% after 5,000 cycles, and has broad prospects in electrochemical energy storage applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119694808A_ABST
    Figure CN119694808A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of new energy materials, in particular to a preparation method, a product and application of a 3D hydrangea-shaped electrode material. The preparation method comprises the following steps: dissolving Co salt, Al salt, urea and hexadecyl trimethyl ammonium bromide in water to prepare a mixed solution A; dipping a substrate in the mixed solution A for hydrothermal reaction to obtain a substrate with a precursor; dissolving Ce salt and an organic ligand in an organic solvent to prepare a mixed solution B; and dipping the substrate with the precursor in the mixed solution B for hydrothermal reaction to obtain the 3D hydrangea-shaped electrode material. The unique 3D hydrangea-shaped electrode material is synthesized through simple hydrothermal reaction, and due to the synergistic effect of the layered double hydroxide and the metal organic framework, the electrode material has high specific capacitance and high cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy material preparation, and in particular to a preparation method, product and application of a 3D hydrangea-shaped electrode material. Background Art

[0002] As people pay more and more attention to environmental protection, the research on renewable energy and sustainable energy storage systems has gradually become a hot topic in the scientific community. Sutherland pointed out that long-term economic energy storage for fixed applications is an important missing factor in realizing a future society dominated by renewable energy. Among many energy storage devices, such as supercapacitors, batteries, fuel cells and electrochromic devices, supercapacitors have received more and more attention due to their high capacitance, good stability, fast charging and discharging process and low maintenance cost. However, their narrow voltage range and low energy density seriously restrict wider application. The charge storage capacity of supercapacitors mainly depends on electrode materials, so it is crucial to develop high-performance electrode materials with high specific capacity and high cycle stability. The progress of electrode materials can not only improve the overall performance of supercapacitors, but also promote their application in fields such as renewable energy and power storage. Therefore, research and innovation on electrode materials is an important direction to improve the technical level of supercapacitors. Summary of the invention

[0003] Based on the above content, the present invention provides a preparation method, product and application of a 3D hydrangea-shaped electrode material.

[0004] To achieve the above object, the present invention provides the following solutions: One of the technical solutions of the present invention is a method for preparing a 3D hydrangea-shaped electrode material, comprising the following steps: Co salt, Al salt, urea and cetyltrimethylammonium bromide (CTAB) were dissolved in water to prepare a mixed solution A; Immersing the substrate in the mixed solution A to perform a hydrothermal reaction to obtain a substrate with a precursor; Dissolving Ce salt and organic ligand in an organic solvent to prepare a mixed solution B; The substrate with the precursor is immersed in the mixed solution B for hydrothermal reaction to obtain the 3D hydrangea-shaped electrode material (CoAl-LDH@Ce-MOF).

[0005] The second technical solution of the present invention is a 3D hydrangea-shaped electrode material prepared according to the above-mentioned preparation method.

[0006] The third technical solution of the present invention is the application of the above-mentioned 3D hydrangea-shaped electrode material in supercapacitors.

[0007] A fourth technical solution of the present invention is a supercapacitor, wherein the electrode material includes the above-mentioned 3D hydrangea-shaped electrode material.

[0008] The present invention discloses the following technical effects: (1) Compared with the existing complex process, the present invention uses Co salt (cobalt nitrate hexahydrate), Al salt (aluminum nitrate nonahydrate), Ce salt and organic ligand (p-aminobenzoic acid) as raw materials to synthesize CoAl-LDH@Ce-MOF, a unique 3D hydrangea-shaped electrode material. The electrode material after CoAl-LDH and Ce-MOF composite provides more reactive sites due to the unique 3D hydrangea structure with increased specific surface area, which can significantly reduce its ion transport resistance to improve capacity performance; in addition, due to the synergistic effect of layered double hydroxide (CoAl-LDH) and metal organic framework (Ce-MOF), the charge transfer path is effectively shortened, so that the electrode material has high specific capacitance and high cycle stability, which provides a new idea for the design and performance optimization of supercapacitor electrode materials.

[0009] (2) In the preparation method of the present invention, the combination of MOFs and LDHs plays an important role in the preparation of advanced electrode materials, which helps to realize high-performance supercapacitors. The electrode material has a high specific surface area and good cycle stability, which is crucial for achieving high-density electrochemical capacitor energy storage. The high specific surface area can provide more active sites, thereby enhancing the charge storage capacity; and the excellent cycle stability ensures the stability of electrical properties during long-term use, thereby improving the overall efficiency and life of the supercapacitor. The 3D hydrangea-shaped electrode material prepared by the present invention has a capacitance retention rate of 88.5% after 5000 cycles. These characteristics make the electrode material have broad prospects in electrochemical energy storage applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0011] Figure 1 (a)~(d) are SEM images of CoAl-LDH and CoAl-LDH@Ce-MOF electrode materials, respectively; among them, (a)~(b) are CoAl-LDH at different magnifications, and (c)~(d) are CoAl-LDH@Ce-MOF at different magnifications.

[0012] Figure 2The CoAl-LDH@Ce-MOF electrode material prepared in Example 1 is 5-100mV·s -1 Cyclic voltammetry curves at different scan rates.

[0013] Figure 3 The CoAl-LDH@Ce-MOF electrode material prepared in Example 1 was 1-10A·g -1 Changes in specific capacitance under different current densities.

[0014] Figure 4 The CoAl-LDH@Ce-MOF electrode material prepared in Example 1 was subjected to 10A·g -1 Cycling performance diagram after 5000 cycles at the same current density.

[0015] Figure 5 BET comparison diagram of CoAl-LDH and CoAl-LDH@Ce-MOF electrode materials prepared in Example 1; wherein (a) is CoAl-LDH and (b) is CoAl-LDH@Ce-MOF. DETAILED DESCRIPTION

[0016] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0017] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0018] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0019] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0020] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0021] By adjusting the structure to achieve the best synergy between metal organic framework materials (MOFs) and layered double hydroxides (LDHs), the advantages of both can be maximized. MOFs can serve as active sites for electrode materials, while LDHs can serve as co-catalysts. Due to the difference in the performance of the two surfaces, the combination can enhance the dispersibility of the material and reduce particle aggregation. In addition, LDHs have excellent mechanical properties and can improve the stability and durability of composite materials. The combination of MOFs and LDHs is expected to create electrode materials with excellent performance, which will be widely used in fields such as renewable energy and electrochemical energy storage, and promote the development of related technologies.

[0022] The present invention provides a method for preparing a high-performance supercapacitor composite electrode material combining MOFs and LDHs, which solves the technical problems that the conductivity and stability of single MOFs or LDHs are low, which hinder their applicability as pseudocapacitor materials after long-term charging and discharging at high current density. In view of the problems of harsh conditions, inconvenient operation, high energy consumption, etc. in the preparation process of the existing synthesis technology, the present invention proposes a method of using nickel foam as a matrix and loading CoAl-LDH on it through a simple hydrothermal synthesis method. In order to further improve the electrochemical performance of the electrode material, Ce-MOF is further compounded on the basis of CoAl-LDH to form a composite electrode material CoAl-LDH@Ce-MOF. Not only is the process simple, environmentally friendly and low-cost, but the prepared material also has a higher specific capacitance, excellent long-term stability and a lower overpotential. In addition, its structural morphology is controllable. The composite electrode material has a unique 3D hydrangea-like structure. This unique structure increases the specific surface area of ​​the electrode material, provides more reaction active sites, and improves the electrochemical performance. At the same time, due to the synergistic effect of layered double hydroxide and metal organic framework, the charge transfer path is shortened and the efficiency of electron transfer is promoted, resulting in excellent electrochemical performance of the electrode material.

[0023] A first aspect of the present invention provides a method for preparing a 3D hydrangea-shaped electrode material, comprising the following steps: Co salt, Al salt, urea and cetyltrimethylammonium bromide (CTAB) were dissolved in water to prepare a mixed solution A; Immersing the substrate in the mixed solution A to perform a hydrothermal reaction to obtain a substrate with a precursor; Dissolving Ce salt and organic ligand in an organic solvent to prepare a mixed solution B; The substrate with the precursor is immersed in the mixed solution B for hydrothermal reaction to obtain the 3D hydrangea-shaped electrode material (CoAl-LDH@Ce-MOF).

[0024] In a preferred embodiment of the present invention, the substrate is nickel foam.

[0025] In a preferred embodiment of the present invention, the mass concentration of urea in the mixed solution A is 0.05% to 1%; the mass concentration of hexadecyltrimethylammonium bromide in the mixed solution A is 0.01% to 0.02%; if the concentration of hexadecyltrimethylammonium bromide exceeds this range, a 3D hydrangea-like morphology cannot be obtained. The concentration of Al salt in the mixed solution A is 0.03 mol / L; the molar ratio of the Co salt to the Al salt is 3:1.

[0026] In the present invention, hexadecyltrimethylammonium bromide plays a role in adjusting the morphology of the prepared electrode material.

[0027] In a preferred embodiment of the present invention, the Co salt is Co(NO3)2·6H2O; and the Al salt is Al(NO3)3·9H2O.

[0028] In a preferred embodiment of the present invention, when preparing the substrate having the precursor, the temperature of the hydrothermal reaction is 90-110° C. and the time is 6-7 hours.

[0029] In a preferred embodiment of the present invention, the molar ratio of the Ce salt to the organic ligand is (0.2-0.25):1; The Ce salt is Ce(NO3)3·6H2O; the organic ligand is p-aminobenzoic acid; and the organic solvent is N,N-dimethylformamide.

[0030] The mass concentration of Ce salt in the mixed solution B is 19-20 mg / mL.

[0031] In a preferred embodiment of the present invention, when preparing the 3D hydrangea-shaped electrode material, the temperature of the hydrothermal reaction is 100-120° C., and the time is 8-10 hours.

[0032] In a preferred embodiment of the present invention, the molar ratio of the Co salt to the organic ligand is (0.28-0.32):1.

[0033] A second aspect of the present invention provides a 3D hydrangea-shaped electrode material prepared according to the above-mentioned preparation method.

[0034] The third aspect of the present invention provides the use of the above-mentioned 3D hydrangea-shaped electrode material in a supercapacitor.

[0035] A fourth aspect of the present invention provides a supercapacitor, wherein the electrode material includes the above-mentioned 3D hydrangea-shaped electrode material.

[0036] The present invention synthesizes 3D nanoflower microsphere structure CoAl-LDH on a substrate (nickel foam) by a hydrothermal synthesis method, grows Ce-MOF in situ on the basis of the 3D nanoflower microsphere structure CoAl-LDH, and finally synthesizes a 3D hydrangea-like structure composite electrode material CoAl-LDH@Ce-MOF, which increases the active sites of the reaction and allows the electrode material to fully contact the electrolyte solution, which is more conducive to the occurrence of electrochemical reactions. In addition, the synergistic effect of CoAl-LDH and Ce-MOF is conducive to the transmission and diffusion of charges on the electrode surface, and the rapid ion effect improves the transmission of electrode capacitance. The prepared CoAl-LDH@Ce-MOF electrode material is in a 2M KOH electrolyte at 1A·g -1 It can provide up to 3513.3 F·g -1 The specific capacitance of the material can reach 88.5% after 5000 cycles of testing, which makes it a potential high-performance electrode material.

[0037] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0038] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0039] Example 1 (1) First, the nickel foam is cut into nickel foam sheets of appropriate size, cleaned, and dried for later use; specifically, the nickel foam is cut into sheets with a specification of 1 cm × 1 cm × 0.07 cm, and then ultrasonically cleaned with acetone for 10 minutes, and then ultrasonically cleaned twice with 3M hydrochloric acid, each time for 10 minutes; then ultrasonically cleaned with deionized water three times, each time for 10 minutes; finally, ultrasonically cleaned with anhydrous ethanol twice, each time for 10 to 30 minutes; then the cleaned nickel foam sheet is placed in a vacuum drying oven, and dried at 80°C for 24 hours, and then the nickel foam sheet is weighed.

[0040] (2) Cobalt nitrate hexahydrate Co(NO3)2·6H2O and aluminum nitrate nonahydrate Al(NO3)3·9H2O were dissolved in deionized water at a molar ratio of 3:1, along with urea and CTAB, and magnetically stirred to mix the solutions evenly to obtain a transparent magenta mixed solution; the concentration of Al(NO3)3·9H2O in the mixed solution was 0.03 mol / L, the concentration of urea was 1%, and the concentration of CTAB was 0.01%.

[0041] (3) The prepared mixed solution was transferred to a polytetrafluoroethylene autoclave, and then the dried and cut nickel foam sheets were placed in the autoclave and sealed; and reacted under hydrothermal conditions at 110° C. for 6 hours, and then cooled to room temperature.

[0042] (4) taking out the nickel foam sheet with the pink precursor in the autoclave, washing it, and drying it; specifically, taking out the nickel foam sheet with the pink precursor in the autoclave in step (3), and then washing it with deionized water and anhydrous ethanol in turn, and finally drying the washed nickel foam sheet in a vacuum drying oven at a constant temperature of 60°C.

[0043] (5) Ce(NO3)3·6H2O (0.3871 g) and p-aminobenzoic acid (0.5451 g) were poured into 20 ml of N,N-dimethylformamide (DMF), stirred for 1 h, and then ultrasonically dispersed for 30 min to obtain a light yellow solution.

[0044] (6) The obtained light yellow solution was transferred to a polytetrafluoroethylene high-pressure reactor, and then the CoAl-LDH nickel foam sheet with a pink precursor was placed in the high-pressure reactor and sealed, and hydrothermally reacted at 100°C for 8 hours, and cooled to room temperature to obtain the CoAl-LDH@Ce-MOF electrode material.

[0045] Figure 1 (a)~(d) are SEM images of CoAl-LDH and CoAl-LDH@Ce-MOF electrode materials respectively; (a)~(b) are CoAl-LDH at different magnifications, and (c)~(d) are CoAl-LDH@Ce-MOF at different magnifications. Figure 1 It can be seen that the CoAl-LDH@Ce-MOF electrode material has more chemically active sites, which can speed up the electrochemical reaction and thus provide greater capacitance.

[0046] The performance of the CoAl-LDH@Ce-MOF electrode material prepared in Example 1 was verified as follows: The electrochemical performance of the electrodes was compared by performing CV tests on the sample electrodes. The potential window was 0-0.6 V and the scan rate was 10-100 mV·s. -1 .

[0047] The specific capacitance of the electrode before and after doping can be determined by performing a GCD test on the sample electrode. The current density is 1~10A·g -1 The formulas for mass specific capacity and specific capacitance tested in a three-electrode system are: (1) (2) Q(C·g -1 ) is the mass specific capacity, C(F·g -1 ) is the mass specific capacitance, I(A) is the set current, Δt(s) is the discharge time, m(g) is the mass of the prepared sample, and ΔV is the potential window.

[0048] This paper uses the constant current charge and discharge cycle test method to study the electrochemical stability of the composite electrode: The CoAl-LDH@Ce-MOF electrode material in Example 1 has high energy density and power density as well as long-term cycle stability. -1 Can provide 3513.3F·g -1 High specific capacitance (such as Figure 3 The prepared supercapacitor (1×1 cm) was charged for 30 seconds and continuously lit up for 10 minutes with 20 parallel small bulbs at 2W, demonstrating its potential in practical applications. In addition, in order to test its long-term static stability, the supercapacitor device was placed for 60 days and then subjected to CV test. The results showed that CoAl-LDH@Ce-MOF / / AC (activated carbon electrode) could still retain 80% of its initial capacitance. The results showed that CoAl-LDH@Ce-MOF has great application prospects as an electrode material for supercapacitors.

[0049] The present invention adopts a two-step solvothermal method to prepare CoAl-LDH@Ce-MOF electrode material, and ensures that the reactants react fully by controlling key factors such as reaction temperature and reaction time, thereby forming a composite electrode material with a specific regular morphology and uniform particle size distribution. This method effectively improves the structural consistency and performance of the material and has potential application value.

[0050] Figure 2 The CoAl-LDH@Ce-MOF electrode material prepared in Example 1 is 5-100mV·s -1 Cyclic voltammetry curves at different scan rates. Figure 2 It can be seen that the electrode material can undergo rapid redox reactions, and it also shows that the electrolyte ions can move quickly on the electrode surface.

[0051] Figure 3The CoAl-LDH@Ce-MOF electrode material prepared in Example 1 was 1-10A·g -1 The change of specific capacitance under current density. Figure 3 It can be seen that at a current density of 1 A·g -1 Can provide 3513.3F·g -1 High specific capacitance.

[0052] Figure 4 The CoAl-LDH@Ce-MOF electrode material prepared in Example 1 was subjected to 10A·g -1 Cycling performance diagram after 5000 cycles at the same current density. Figure 4 The results show that the CoAl-LDH@Ce-MOF electrode material has excellent cycling stability.

[0053] Figure 5 The BET comparison diagram of CoAl-LDH and CoAl-LDH@Ce-MOF electrode materials prepared in Example 1; (a) is CoAl-LDH, and (b) is CoAl-LDH@Ce-MOF. Figure 5 It can be seen that the CoAl-LDH@Ce-MOF electrode material can increase the density of active sites and the rapid transfer / diffusion of electrolyte ions.

[0054] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a 3D hydrangea-shaped electrode material, characterized in that: The following steps are involved: Dissolving Co salt, Al salt, urea and hexadecyltrimethylammonium bromide in water to prepare a mixed solution A; Immersing the substrate in the mixed solution A to perform a hydrothermal reaction to obtain a substrate with a precursor; Dissolving Ce salt and organic ligand in an organic solvent to prepare a mixed solution B; The substrate with the precursor is immersed in the mixed solution B for hydrothermal reaction to obtain the 3D hydrangea-shaped electrode material.

2. The method for preparing the 3D hydrangea-shaped electrode material according to claim 1, characterized in that: The mass concentration of urea in the mixed solution A is 0.05%-1%; the mass concentration of hexadecyltrimethylammonium bromide in the mixed solution A is 0.01%-0.02%; the concentration of Al salt in the mixed solution A is 0.03 mol / L; and the molar ratio of the Co salt to the Al salt is 3:

1.

3. The method for preparing the 3D hydrangea-shaped electrode material according to claim 1, characterized in that: The Co salt is Co(NO3)2·6H2O; the Al salt is Al(NO3)3·9H2O.

4. The method for preparing the 3D hydrangea-shaped electrode material according to claim 1, characterized in that: When preparing the substrate with the precursor, the temperature of the hydrothermal reaction is 90-110° C. and the time is 6-7 hours.

5. The method for preparing the 3D hydrangea-shaped electrode material according to claim 1, characterized in that: The molar ratio of the Ce salt to the organic ligand is (0.2-0.25):1; The Ce salt is Ce(NO3)3·6H2O; the organic ligand is p-aminobenzoic acid; the organic solvent is N,N-dimethylformamide; The mass concentration of Ce salt in the mixed solution B is 19-20 mg / mL.

6. The method for preparing the 3D hydrangea-shaped electrode material according to claim 1, characterized in that: When preparing the 3D hydrangea-shaped electrode material, the temperature of the hydrothermal reaction is 100-120° C. and the time is 8-10 hours.

7. The method for preparing the 3D hydrangea-shaped electrode material according to claim 1, characterized in that: The molar ratio of the Co salt to the organic ligand is (0.28-0.32):

1.

8. A 3D hydrangea-shaped electrode material prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the 3D hydrangea-shaped electrode material as claimed in claim 8 in a supercapacitor.

10. A supercapacitor, characterized in that: The electrode material comprises the 3D hydrangea-shaped electrode material according to claim 8.

Citation Information

Patent Citations

  • Preparation method of flower-shaped CoAl layered doubled hydroxide electrode material

    CN107195485A

  • Preparation method of electrode made of spiny metal hydroxide penetration type growth MOF

    CN113903604A

  • Organic ligand modified transition metal layered hydroxide electro-catalytic material as well as preparation method and application thereof

    CN113981469A

  • Preparation method and electro-catalysis application of MOF-coated LDH composite material

    CN114606511A

  • Preparation method and application of N-Ni / N-CeO2 / nickel electrode

    CN114836788A